2021
DOI: 10.1186/s12864-021-07675-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-based sex classifier to predict sex and identify sex chromosome aneuploidy

Abstract: Background Sex is an important covariate of epigenome-wide association studies due to its strong influence on DNA methylation patterns across numerous genomic positions. Nevertheless, many samples on the Gene Expression Omnibus (GEO) frequently lack a sex annotation or are incorrectly labelled. Considering the influence that sex imposes on DNA methylation patterns, it is necessary to ensure that methods for filtering poor samples and checking of sex assignment are accurate and widely applicable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Secondly, the differing normalisation methods applied to DNAme microarray data. Previous research has shown that the methylation levels of CpG sites on the X chromosome differ largely between males and females [ 29 ] and, thus, normalisation methods which normalise array data indiscriminately with CpG sites on the autosomes introduce large technical biases for autosomal CpGs [ 30 ]. Using normalisation methods, which do not handle the technical bias introduced by sex chromosomes, will therefore lead to many autosomal CpG sites being falsely associated with sex and further, a higher number of autosomal CpGs being incorrectly identified as male-biased CpGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the differing normalisation methods applied to DNAme microarray data. Previous research has shown that the methylation levels of CpG sites on the X chromosome differ largely between males and females [ 29 ] and, thus, normalisation methods which normalise array data indiscriminately with CpG sites on the autosomes introduce large technical biases for autosomal CpGs [ 30 ]. Using normalisation methods, which do not handle the technical bias introduced by sex chromosomes, will therefore lead to many autosomal CpG sites being falsely associated with sex and further, a higher number of autosomal CpGs being incorrectly identified as male-biased CpGs.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of whole blood DNA from participants were obtained following the protocol described in [ 88 ]. Raw signal intensities were processed using the R package bigmelon [ 29 ] and watermelon [ 89 ] from idat files. Prior to normalisation of the data, outlier samples were identified using principal component analysis and subsequently removed from the data set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age class designations were confirmed based on morphological features (Pruitt, 1954; Rudd, 1955). Shrews were sexed by gel electrophoresis of PCR amplicons of the Y chromosome-linked SRY gene (Cervantes et al, 2013; Matsubara et al, 2001) using custom primers (Table S1); sex assignments were subsequently validated with the methylation assay (Wang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Then the raw methylation beta values is calculated as: , where M denotes methylated intensities and U denotes unmethylated intensities. For all those samples, we estimated their sex by using the estimateSex function [48] from the wateRmelon package [49], any samples with mismatches between its reported sex and the estimated sex from the DNAm data were excluded for downstream analysis. Also, the beta value density distributions of samples within each dataset were manually checked to remove any samples with abnormal distribution profiles.…”
Section: Methodsmentioning
confidence: 99%